Phenomenon of Chemical Binding of Air Nitrogen with the Formation of Nitrides Crystal Phases in the Process of Burning of Metals, Boron and Silicon Powders; Applied Particle Technology - Ilyin A. P. Aleksandr Petrovich (2009, 2009)
The research stages of nitrogen chemical accumulation during metals, boron and silicon powders burning in air,with the formation of independent crystal phases of nitrides are presented in the paper. The extraordinarycharacteristic of this phenomenon is connected with a contradiction: thermodynamic calculations show that nitridesare being oxidized by oxygen. It has been shown that the phenomenon is interdisciplinary: its manifestations areapplicable in many spheres of science and technique. A probable mechanism is proposed regarding the formation ofnitrides under high temperature conditions in the presence of air oxygen.